Analysis of the Application of Accountability Accounting as a Cost Control Tool at Prof. Dr. R.D Kandou Hospital Manado - Tarega, Simon; Karamoy, Herman; Gerungai, Natalia Y. T. (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research was conducted at RSUP Prof. R.D. Kandou Manado, which is located in Malalayang District, Manado City. As an institution engaged in the health sector, this research focused on the use of responsibility accounting as a tool to control operational costs at the hospital. This data is also used to assess the performance of managers in each responsibility center, as it focuses on the linkage between managers' responsibilities and the implementation of predetermined plans The main issue raised is how effective the application of responsibility accounting is in supporting cost control in this organization. This research uses a qualitative descriptive approach. Based on the results of the study, it is concluded that RSUP Prof. Dr. R.D. Kandou Manado has implemented responsibility accounting well as a cost control tool. This is indicated by the fulfillment of the requirements for the application of responsibility accounting adequately in the hospital.